The rubber elongation factor of rubber trees ( Hevea brasiliensis) is the major allergen in latex - Czuppon, Adam B.; Chen, Z.; Rennert, Stefan; Engelke, Thomas; Meyer, Helmut E.; Heber, Markus; Baur, Xaver (Journal of allergy and clinical immunology, 1993)
Background: Allergy to latex-containing articles is becoming more and more important because it can result in unexpected life-threatening anaphylactic reactions in sensitized individuals. Methods: A protein of 58 kd with an isoelectric point of 8.45 was purified from raw latex and from latex gloves and identified as the major allergen, completely blocking specific IgE antibodies in the serum of latex-sensitized subjects. The allergen is a noncovalent homotetramer molecule, in which the 14.6 kd monomer was identified, by amino acid composition and sequence homologies of tryptic peptides, to be the rubber elongation factor found in natural latex of the Malaysian rubber tree. Results: Competitive immunoinhibition tests showed that the starch powder covering the finished gloves is the airborne carrier of the allergen, resulting in bronchial asthma on inhalation. The purified allergen can induce allergic reactions in the nanogram range. Conclusion: The identification of the allergen ( Hev b I) may help to eliminate it during the production of latex-based articles in the future.